Effectiveness Of 3 Prenatal Yoga Poses To Reduce Back Pain In Pregnant Women Tm Iii At Bpm Midwife Susi Grogol Sukoharjo - Pramita Sandy, Pramita Sandy Ulya Imannura; Anna Mariana (Journal for Quality in Public Health, 2025)
Back pain during pregnancy is a condition of discomfort that is most often felt by pregnant women and generally occurs in the third trimester of pregnancy. In Indonesia itself, out of 180 pregnant women studied, around 47% experienced back pain. Pregnant women in the third trimester practiced 3 prenatal yoga movements designed to reduce back pain in pregnant women in the third trimester. The pre-experimental design is a one-group pretest-posttest design where one group of subjects and observations were carried out before and after treatment. The population in this study were all pregnant women in the third trimester with sample criteria being pregnant women who had a gestational age of 28-40 weeks and without any complications during pregnancy as many as 20 people. Data analysis used normality tests, univariate analysis and bivariate analysis using the Wilcoxon test. The results of the data normality test showed a p value <0.05, this means that the data is not normal, so the bivariate test used was the silcowon test. Statistical results with the Wilcoxon test showed that the value = 0.001 (p <0.05) which indicates that 3 prenatal yoga movements are effective in reducing back pain in pregnant women in the third trimester. There is effectiveness of 3 prenatal yoga movements to reduce back pain in pregnant women in the third trimester.